The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1759-7714.13007
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation (ECMO)‐assisted intratracheal tumor resection and carina reconstruction: A safer and more effective technique for resection and reconstruction

Abstract: Carina resection and reconstruction is required when a tracheal tumor invades the tracheal carina. It is a relatively complicated surgical procedure that requires complex reconstruction to maintain airway continuity. The technical difficulty lies in minimizing the influence of anesthetic endotracheal intubation and maintaining good ventilation function during surgery by establishing appropriate ventilation channels, which are contradictory in many cases. Therefore, in order to achieve the optimal surgical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Hypoxia and hypoperfusion during ECMO may also cause neurological complications, including hemorrhage, seizures, and infarction (2,4,5,26). Compared to VA-ECMO, venous cannulation is less invasive, and VV-ECMO avoids the risk of arterial injury and minimizes hemodynamic disturbance (6,13), which may cause thromboembolic venous disease, recirculation, and superior cava syndrome (7). However, in this study, no VV-ECMO-related complications were observed.…”
Section: Discussionmentioning
confidence: 60%
“…Hypoxia and hypoperfusion during ECMO may also cause neurological complications, including hemorrhage, seizures, and infarction (2,4,5,26). Compared to VA-ECMO, venous cannulation is less invasive, and VV-ECMO avoids the risk of arterial injury and minimizes hemodynamic disturbance (6,13), which may cause thromboembolic venous disease, recirculation, and superior cava syndrome (7). However, in this study, no VV-ECMO-related complications were observed.…”
Section: Discussionmentioning
confidence: 60%
“…Under this condition, ECMO can be used to maintain the oxygen supply without tracheal intubation or high-frequency ventilation catheter manipulation during the procedure. The first case report of an ECMO-assisted intratracheal tumor resection and carina reconstruction was published in 2019, which was an open surgery ( 7 ). On the other hand, tracheal resection is traditionally approached with a right lateral thoracotomy or median sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, it is contradictory to guarantee adequate blood oxygenation and to gain excellent visualization of the surgical field. We thought extracorporeal membrane oxygenation (ECMO) might help us achieve the optimal surgical outcome ( 7 ). Finally, we innovatively integrated ECMO-assisted and uniportal thoracoscopic techniques for the first time, perfectly achieving simultaneous tracheal tumor resection and tracheoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…9 As a result, either the lesion requiring repair or the surgery itself often impedes the use of traditional intubation techniques during central airway surgery. 11,12 The unique challenges to airway management during central airway surgery necessitate a non-traditional adjunct therapy such as ECLS to maintain hemodynamic stability and adequate gas exchange. 7 Furthermore, in the setting of emergent, lifethreatening central airway injury, where detailed preoperative intubation planning is not possible, the use of ECLS may be the only viable option to allow successful perioperative oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…7 This challenge arises from the dual nature of central airways as both the site of surgical intervention and the main avenue for maintaining ventilation and oxygenation. 11,12 Distal airway management through conventional intubation and jet ventilation both require cross-field ventilation in order to maintain adequate gas exchange. 11,12 However, in the setting of central airway surgery, the crossfield setup required for these techniques can obstruct the operative field, increase tension on newly created anastomoses, and can lead to inefficient perioperative oxygenation.…”
Section: Introductionmentioning
confidence: 99%